Use of experimental periodontitis induction in mice for clinical studies: methods and results (Brazilian Journal of Health Research, 2022)
Introduction: Studies have sought to use methods for inducing experimental periodontitis in mice to analyze the inflammatory process and alternative therapeutic factors. Objectives: To carry out an integrative literature review on the methods and results of research carried out in mice in order to induce an inflammatory process of periodontitis. Methods: Use qualitative methodology and definition of the guiding question: What are the main methods and results in the induction of experimental periodontitis in mice? The MeSHterms: “Periodontitis” and “Mice” were used to search for scientific articles in the PubMed database. 4,192 full-length works were found; of these, 16 articles were duplicated in the search strategies, thus totaling 7 selected articles. Results: The inflammatory process of periodontitis in mice can occur more effectively with the use of ligation than with gavage, as there is a response by the immune cells to the attack of the aggressor agent, and the ligature is an agent that will be constantly and commonplace in the installed region than by gavage. Among the methodologies for inducing periodontitis, those with application of the bacterial pathogen directly to the gingival tissue were observed; application of LPS from P. gingivalis; placing a ligature with silk thread soaked with P. gingivalis; and placing a ligature with silk thread without bacteria soaking. Conclusion: In this animal model for the study of periodontitis, some physiological changes were observed, such as immunological disorders and changes in heart rate. Therefore, the results of this review answered the guiding question established in the methodology.
Keywords: Mice; Periodontitis; Porphyromonas; Ligature